Recovery plan strategy on the delay construction project - Ku Ismail, Ku Adenan (2004)
Delay is one of the most common problems in the construction industry. Generally, delays can be classifies into three types which is compensable delays or excusable delays with compensation, non-excusable delays or excusable delays without compensation. In order to control and avoid any further delays, immediate action on recovery plan strategy must be taken from all parties involve in construction project. As people say preventive is better than cure, identification of root cause of delay is very important to contractor as a preventive action to prevent the delays. While recovery plans strategy can be used as a management tool to minimize the delays. This study mainly discussed the causes of delay and appropriate recovery plan strategy to overcome the delay in construction project. A survey of randomly selected sample of 48 respondent consist 28 contractors (58.3%), 18 consultant engineers/architects (37.5%) and 2 represent client/owner (4.2%). This study also involve a study case on the delay and recovery plan strategy taken by Lankhorst Pancabumi Contarctors Sdn. Bhd. (LPCSB) as a main contractor at TUDM Subang, Selangor. The survey showed that financial delay factor was ranked the highest and communication factor was ranked the lowest. The most important delays in category of compensable delays (cause by client) were delay in contractor progress payment, late in possession of site, delays in producing design/drawing/detailing, inadequate information from consultant and waiting for material approval. The most important delays in category of non-excusable delays (cause by contractor) were financial problem, shortage of skill workers, shortage of plan/equipment, shortage of material, and slow mobilisation. The most important delays in category of excusable delays (cause by third party) were act of God such as inclement weather and natural disaster, While on the recovery plan strategy, the most important step to overcome the delays is providing the fund according to cash flow required, Application of extra working hour, Additional of resources (manpower, material and machinery) and Introduction of new construction method.